Prototipe Media Pembelajaran Rambu Lalu Lintas Berbasis Android - Andi Tejawati; Muhammad Bambang Firdaus; Muhammad Nur Ihwan; Faza Alameka; M Khairul Anam (METIK JURNAL, 2021)
This study is motivated by motorists' lack of knowledge and discipline when it comes to traffic signs, which leads to frequent traffic accidents, congestion, and other issues on the road. The problem formulation is how to design and develop an Android-based traffic learning media application. The goal of this research is to provide motorists with information about road signs. The purpose of this research is to examine the literature on the theory of instructional media and the various types of android-based application development. The black box method was used to test this application. This study yielded an android-based traffic learning media application. Based on the test results, it is possible to conclude that this application was created to assist motorists in locating traffic signs on the highway